Property Market Research (SGP 3113): Instructor's Comments on Students’Lab Work 2. - Mar Iman, Abdul Hamid (2008)

(untitled)
Containing brief comments on students' answers for Lab Work 2 from the subject instructor. Sample of proposed answers are also given.